2023
DOI: 10.3389/fnut.2023.1159809
|View full text |Cite
|
Sign up to set email alerts
|

Specific health beliefs mediate sex differences in food choice

Abstract: ObjectiveAlthough sex differences in dietary habits are well documented, the etiology of those differences is still a focus of research. The present study examines the role of specific health beliefs regarding healthy amounts of food for food choice and its relation to sex, more specifically, the assumption that sex differences in food choices are mediated by differentiating health beliefs.Method212 German participants (44.3% female) aged 18–70 answered an online self-report questionnaire on their dietary habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The study focused on the perceptions of the level of processing of sports foods rather than the foods themselves and perceptions and reasons for consumption [ 29 ], which differed to this present study. It is unclear exactly why there has been a shift in sports food consumers; however, it could be related to the intersection between gender differences in health beliefs, where females rate ‘health’ as a more important factor when making sports food choices [ 30 ]. Furthermore, it could be driven by an increased perception that supplementation is needed to ensure adequate nutrient levels, likely driven by the aggressive marketing of sports foods to non-athletes via social media channels [ 31 ] promoting the use of these products to this population.…”
Section: Discussionmentioning
confidence: 99%
“…The study focused on the perceptions of the level of processing of sports foods rather than the foods themselves and perceptions and reasons for consumption [ 29 ], which differed to this present study. It is unclear exactly why there has been a shift in sports food consumers; however, it could be related to the intersection between gender differences in health beliefs, where females rate ‘health’ as a more important factor when making sports food choices [ 30 ]. Furthermore, it could be driven by an increased perception that supplementation is needed to ensure adequate nutrient levels, likely driven by the aggressive marketing of sports foods to non-athletes via social media channels [ 31 ] promoting the use of these products to this population.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the motivation underlying how boys and girls eat differs and is largely consistent regardless of country. Health promotion endeavors targeting diet should thus incorporate gender-unique motivators behind eating to support their likelihood of success (6,7,19). Future studies are also needed to fully untangle how both gender and sex impact adolescents' dietary habits (10, 23).…”
Section: Discussionmentioning
confidence: 99%
“…Though the trends in body shape found in this review are not original (27,29,92,93), our study contributes to understanding the larger picture of adolescents' motivation behind eating based on gender. Specifically, we call on researchers who create dietary interventions targeting adolescents to consider focusing on using language and content that speaks to gender-diverse motivators, including body shape, fitting in, and pursuing autonomy (e.g., focus on autonomy and personal control among boys vs. highlighting social relationships and pressures among girls) (6,7,10,23,88). We also call on research to clarify the role of athletic performance in adolescents' dietary choices, as this review only identified this influence among boys.…”
Section: Self-motivators Gender and Dietary Habitsmentioning
confidence: 99%
See 2 more Smart Citations